The decline of agriculture in rural Transkei: Êºthe case of Mission Location in ButterworthÊº - Ngcaba, Siyanda Vincent (Rhodes University, Faculty of Humanities, Department of Sociology, 2003)
The following dissertation sets out to investigate the decline of agriculture in Mission location at Butterworth, Transkei, using the Rehabilitation Scheme as a benchmark. The scheme was introduced in 1945 to combat soil erosion and improve agriculture in the African reserve areas, as the South African government claimed. The dissertation argues that this claim by the government served to mask the real intentions behind the scheme namely, to regiment the migrant labour system by depriving as many Africans as possible of productive land so that they were unable to fully subsist by means of agriculture. This is further shown by analysing the impact of the Rehabilitation scheme in Mission location in which a substantial number of people lost arable land as a result of the implementation of the scheme in 1945. These people were consequently denied the wherewithal to subsist by agriculture. Moreover, the efforts of the government resulted to a modernisation of agriculture by making it more cash-based- for example through the introduction of fencing, the need for tractors as a result of a decline in stock numbers (in part as a result of stock culling). Most people could hardly afford this type of agriculture and were consequently forced off the land. The dissertation concludes that indeed the decline of agriculture in Mission location can be linked to the changing agricultural and land-holding practices brought about by the government- especially the introduction of the Rehabilitation scheme.
Keywords: Agriculture -- South Africa -- Transkei; Land use -- South Africa -- Transkei; Land tenure -- South Africa -- Transkei